PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASI TERHADAP LOYALITAS KARYAWAN HAZOTEL SEMARANG - Iqbal Reza Pratama; Hadiahti Utami; Inayah Inayah (JOBS (Jurnal Of Business Studies), 2019)
Employee’s loyalty is one of problems faced by Hazotel Semarang.  This problem is related to transformational leadership style and organizational commitment.  This research aims to determine the influence of transformational leadership style and organizational commitment on employee’s loyalty at Hazotel Semarang. The independent variables in this research are transformational leadership style (X1) and organizational commitment (X2), where employee’s loyalty (Y) as dependent variable. The type of this research is quantitative research metohod.  To determine the number of the samples, Saturation sampling is used in this research whereas 24 person as the number of all population member are included  in this research.  The source data obtained by the primary data for distributing the questionnaire and secondary data by observation, interview, and literature study. The data collected using questionnaire is based on specified indicators. The result of the partial analysis showed that transformational leadership style has positive influence and significant on employee’s loyalty (t count > t table, 2,553 > 2,074). While organizational commitment has positive influence but not significant on employee’s loyalty, t count < t table, (1,111 < 2,074). The result of the simultan analysis showed that transformational leadership style and organizational commitment has positive influence and significant on employee’s loyalty, F count > F table (7,414 > 3,47).